FIVE YEARS CHARACTERISTIC OF URETERAL TRAUMA IN TERTIARY HOSPITAL IN WEST JAVA FROM 2013-2017 - Tambah, Adi Bachtiar; Adi, Kuncoro (Indonesian Urological Association, 2021)
Objective: This study aims to determine the characteristics of trauma patients, especially ureteral trauma in Hasan Sadikin General Hospital and expected to be used as data for trauma nationally. Material & Methods: This study was descriptive. Retrospective data collection is taken from medical records of ureteral trauma from 2013 until August 2017 at Hasan Sadikin General Hospital, Bandung. The data obtained are gender, mechanism of trauma, and management of ureteral trauma. Results: A total of 20489 cases of trauma handled in Hasan Sadikin General Hospital, 2.3% is a case of urogenital trauma and 40 of which are cases of ureteral trauma (0.19%). Most ureteral trauma patients are female (90%). Based on the trauma mechanism, 39 patients iatrogenic trauma (97.5%) and 1 patient gunshot wounds (2.5%). From iatrogenic ureteral trauma, 36 patients (90%) had iatrogenic trauma from the gynecological procedure, 5% as a result of the urological procedure, and 2.5% due to gastrointestinal procedure. Management of ureteral trauma is 47.5% ureteroureterostomy and 25% ureteroneocystostomy. Conclusion: Most cases of ureteral trauma are experienced by women, and most commonly due to iatrogenic trauma. Iatrogenic ureteral trauma caused by gynecology procedure is the most common.